Design of temperature control system in rotary type cloth dryer to optimize drying time - Ragani, Nabilla Sukama; Aisyah, Putri Yeni; Hija, Akhmad Ibnu; Ashiddiqi, Muhammad Roy; Pratama, I Putu Eka Widya (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2025)
Erratic climate change and limited drying space in apartments lead to an inefficient clothes drying process. Commercial clothes dryers are often sub-optimal in terms of drying duration and energy efficiency. Clothes dryer technology without dependence on solar energy has been widely circulated, but has disadvantages, such as long drying time and high price. This research develops a temperature control system on a prototype rotary-type clothes dryer to optimize drying time. The dimensions of the prototype are 0.65 cm x 0.70 cm x 90 cm, the power consumption of the cloth dryer is 598.4 watts, using a DHT22 sensor to control the temperature. The motor speed rotates at 730-790 rpm, with the fan rotating constantly, and the heater has temperature set points of 43°C (upper) and 45°C (lower). The system applies an on-off control method to achieve the desired temperature set point. The test results show that the temperature control system in the clothes dryer with the on-off method is successful with an error rate of 0.74% for a mass of 1 kg of clothes. This error rate meets the set standard of no more than 5%, indicating that the on-off control system works as expected.